Childhood anemia - A study in tribal area of Mohana block in Orissa - Sahu T; Sahani N; Patnaik L (Wolters Kluwer Medknow Publications, 2007)
Background : Anemia is widely prevalent in India and affects both sexes and all age group. Although the National Anemia Prophylaxis Programme (NAPP) has been set up in all states of the country since 1970, the benefits have not yet been appreciated in the target population. Objective : 1. To assess the prevalence of anemia and its severity in tribal children. 2. To find out age & sex wise distribution of Hb level in these children. 3. To explore different underlying factors of development of anemia. Methods : The present study is a cross sectional study conducted in tribal villages of Mohana block in Gajapati district of Orissa. A total of 599 tribal children in the age group 6 month - 14 years were recruited from August 2004 to February 2005. The study variables included age, sex, Hb level, food consumption and clinicoepidemiological factors which were analysed by simple proportion and Z test. Results : About 94% of under five children were found to be anemic and 8.8% of them were severely anemic. Almost all children of age group 5-14 years were anemic, amongst them 59.4% were moderately anemic and 5. 4% were severely anemic. There is no significant difference in mean Hb level between male and female in both the age groups. It was significantly more in the age group of 5-14 years. About 94% were taking food of low iron bioavailability. Pallor was found in 33.6% and H/O irregular fever in 28.7% of children. 26.9% children had splenomegaly. Only 2.3% children had taken IFA supplementation in last one year. Conclusions : Anemia is a major health problem in tribal children. Reorientation of primary health care functionaries to cover the children under NNAPP with the help of ICDS workers and school authorities.